2010
DOI: 10.1590/s0034-737x2010000300014
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos, produção e qualidade do capim braquiária em solos corrigidos com calcário e escória silicatada

Abstract: Chemical attributes, production and quality of signal grass in soils amended with limestone and calcium silicate slagPastures are the basis of cattle production systems, evidencing their importance and the need for other management practices that result in higher efficiency of these systems. This study aimed to evaluate the soil chemical properties (pH, Ca, Mg and H+Al), the potential production and the chemical composition of signal grass (Brachiaria decumbens Stapf) in soil amended with different limestone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Santana et al (2010) also reported the effect of limestone and silicate slag application on chemical attributes of the soil, and production and quality of brachiaria forage; increases in soil magnesium were also observed in function of the corrective levels, after application of slag.…”
Section: Resultsmentioning
confidence: 92%
“…Santana et al (2010) also reported the effect of limestone and silicate slag application on chemical attributes of the soil, and production and quality of brachiaria forage; increases in soil magnesium were also observed in function of the corrective levels, after application of slag.…”
Section: Resultsmentioning
confidence: 92%
“…Em contrapartida, a espécie B. decumbens promoveu à P. dubium a menor TCA (Tabela 2), corroborando com Ikeda et al (2013) que afirmam que a espécie se torna uma planta indesejável, quando utilizada em áreas que não sejam de pastagens, em função de sua rusticidade e do difícil controle. A espécie B. decumbens, trata-se de uma excelente forrageira, perene e com grande produção de massa foliar de boa qualidade, resistente ao pastejo e ao pisoteio (SANTANA et al, 2010). Além disso, Toledo et al (2000) ressaltam a agressividade e o potencial colonizador dessa espécie forrageira invasora comprometendo os processos de regeneração natural.…”
Section: Resultsunclassified
“…According to Fukushima and Paneto (1995), a lignin is associated with a break in the nutrient digestion of the fraction fibrous food and, considering that the maturity of the plants promotes increased lignin content, decreased nutritional value of mature plants. Santana et al (2010a) observed that the nutritional composition of Urochloa decumbens, assessed using NDF and ADF, was not affected by acidity correction, except in the third cut in the lime application provided higher NDF content in the silicate. The NDF increased from the first to the third cut, whereas ADF showed the opposite trend; this indicated lower degradability with increasing cutting interval structures.…”
Section: Nutritional Value Of Urochloa Convert Hd364mentioning
confidence: 86%
“…Also, NDF, ADF, and hemicellulose were not affected by the application of CaSiO 3 to the Ox1, Ult, and Ox2 soils (Table 4). Santana et al (2010a) evaluated the nutritional value of Urochloa decumbens in soil amended with different rates of limestone and silicate and found that the nutritional composition of Urochloa decumbens, assessed using NDF and ADF, was not affected by acidity correction, except in the third cut where the application of lime resulted in a higher NDF content. ** and * significant at 1% and 5% probability, respectively, by F test; ns not significant.…”
Section: Nutritional Value Of Urochloa Convert Hd364mentioning
confidence: 99%